Portaria PRCE n° 491, de 15 de julho de 2022 - (:unkn) unknown (DMPF-e, Brasília, DF, 19 jul. 2022. Caderno administrativo, p. 8., 2022)
Altera o artigo 1º da Portaria Gab/Chefia nº 412, de 21 de junho de 2022.